1981
DOI: 10.1113/jphysiol.1981.sp013608
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of binocular depth mechanisms in areas 17 and 18 of the cat visual cortex

Abstract: 1. The retinal disparity sensitivity of neurones in areas 17 and 18 of the cat visual cortex was examined. The response of each cell to an optimally oriented slit was measured as disparity was varied orthogonally to the receptive field orientation. Eye movements were monitored with a binocular reference cell simultaneously recorded in area 17 (Hubel & Wiesel, 1970). 2. Two types of disparity‐sensitive cells were found, similar to those observed in the monkey by Poggio & Fischer (1977). The first type, tuned ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
179
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(200 citation statements)
references
References 51 publications
20
179
1
Order By: Relevance
“…Fortunately, a method for determining the responses of binocular complex cells has recently been proposed by Ohzawa et al (1990) based on their quantitative physiological studies (see also Ferster, 1981). These investigators found that a binocular complex cell in the cat primary visual cortex can be simulated by summing up the squared responses of a quadrature pair of simple cells, and the simple cell responses, in turn, can be simulated by adding the visual inputs on their left and right receptive fields (see Figure 5).…”
Section: Physiological Computation Of Binocular Disparitymentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, a method for determining the responses of binocular complex cells has recently been proposed by Ohzawa et al (1990) based on their quantitative physiological studies (see also Ferster, 1981). These investigators found that a binocular complex cell in the cat primary visual cortex can be simulated by summing up the squared responses of a quadrature pair of simple cells, and the simple cell responses, in turn, can be simulated by adding the visual inputs on their left and right receptive fields (see Figure 5).…”
Section: Physiological Computation Of Binocular Disparitymentioning
confidence: 99%
“…These curves alone are not very useful from a computational point of view because a response can be read from a disparity tuning curve only when the stimulus disparity is already known. We need a quantitative procedure for computing an unknown disparity in a pair of retinal images from the responses of complex cells to the images.Fortunately, a method for determining the responses of binocular complex cells has recently been proposed by Ohzawa et al (1990) based on their quantitative physiological studies (see also Ferster, 1981). These investigators found that a binocular complex cell in the cat primary visual cortex can be simulated by summing up the squared responses of a quadrature pair of simple cells, and the simple cell responses, in turn, can be simulated by adding the visual inputs on their left and right receptive fields (see Figure 5).…”
mentioning
confidence: 99%
“…Several computational studies have examined matching by correlation (Tyler and Julesz, 1978;Jenkin and Jepson, 1988;Cormack et al, 1991;Kanade and Okutomi, 1994;Weinshall and Malik, 1995). Furthermore, the properties of binocular neurons in the striate cortex suggest that the estimation of disparity begins with signals closely related to binocular correlation measured after the image is filtered by monocular receptive fields (Ferster, 1981 5-8) pointed out the mathematical equivalence between interocular correlation and the disparity energy calculation that underlies binocular interaction in V1 neurons (Ohzawa et al, 1990;Cumming and Parker, 1997). The accompanying paper (Nienborg et al, 2004) suggests that the size of V1 receptive fields limits the ability of single neurons to detect spatial variation in disparity.…”
Section: Description Of the Algorithmmentioning
confidence: 99%
“…In fine stereopsis, subjects can easily fuse the images even when the eye vergence does not change and the magnitude of perceived depth increases linearly as disparity increases, while in coarse stereopsis subjects report frequently diplopia of the two images when stimuli are presented briefly and the magnitude of perceived depth does not increase linearly as disparity increases. Recently, the neurophysiological substrata of the two different subsystems were found (Fernster, 1981;Poggio & Fischer, 1977;Poggio & Talbow, 1981).…”
mentioning
confidence: 99%